Trends of the macroscopic behaviors of energetic compounds: insights from first-principles calculations. Issue 43 (24th October 2019) - Sun, Chuli; Zhang, Weijing; Lü, Yongjun; Wang, Feng; Guo, Wei; Zhang, Tonglai; Yao, Yugui
Abstract : Studies on the relationship between the microscopic properties and macroscopic behaviors of energetic compounds may provide clues for the synthesis and assessment of novel high energy density materials. Abstract : Understanding the structure–property relationships of energetic compounds is challenging. Herein, by including the experimental data, we systematically evaluated the microscopic characteristics of a series of transition metal carbohydrazide perchlorate (TMCP) complexes (MnCP, FeCP, CoCP, NiCP, ZnCP, and CdCP) by first-principles calculations. The calculated properties, i.e., lattice enthalpy, bulk modulus, and electronic structures, were correlated with their thermal decomposition temperatures and impact sensitivities, which indicated that the stability and sensitivity of the TMCP complexes were greatly changed through coordination with different metal ions. The trend was that a large lattice enthalpy indicated a better thermal stability. Complexes with a high impact sensitivity tended to have a smaller bulk modulus and pseudo-gap. The ultra-high impact sensitivity of FeCP may have been related to the unstable spin state with respect to the volume change in the lattice. The calculated bond order and bond dissociation energy did not fully reflect the impact and friction sensitivities in this study. In addition, the combination of crystal properties and local bond information may better describe the sensitivity trend for the TMCP energetic compounds. This analysis can be applied to other energetic compounds and may provide clues for the synthesis and assessment of novel energetic compounds.